2016
DOI: 10.1002/minf.201600041
|View full text |Cite
|
Sign up to set email alerts
|

Docking-based Design of Galantamine Derivatives with Dual-site Binding to Acetylcholinesterase

Abstract: The enzyme acetylcholinesterase is a key target in the treatment of Alzheimer's disease because of its ability to hydrolyze acetylcholine via the catalytic binding site and to accelerate the aggregation of amyloid-β peptide via the peripheral anionic site (PAS). Using docking-based predictions, in the present study we design 20 novel galantamine derivatives with alkylamide spacers of different length ending with aromatic fragments. The galantamine moiety blocks the catalytic site, while the terminal aromatic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 74 publications
2
33
0
Order By: Relevance
“…Previous X‐ray structures of the complexes AChE‐GAL derivatives show that both axial and equatorial orientations of the N‐linkers are possible . Recently, it was found that both orientations gave similar docking scores . The protocol was optimized in several steps using two training sets of galantamine derivatives, as described elsewhere .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous X‐ray structures of the complexes AChE‐GAL derivatives show that both axial and equatorial orientations of the N‐linkers are possible . Recently, it was found that both orientations gave similar docking scores . The protocol was optimized in several steps using two training sets of galantamine derivatives, as described elsewhere .…”
Section: Methodsmentioning
confidence: 99%
“…[20,24] Recently, it was found that both orientations gave similar docking scores. [36] The protocol was optimized in several steps using two training sets of galantamine derivatives, as described elsewhere. [28,39] At each step, the correlation between the docking scores and the pIC 50 (−logIC 50 ) values of the training compounds was evaluated.…”
Section: Materials and Methods 21 | Docking Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…The docking simulations were performed by GOLD v. 5.2. (CCDC Ltd., Cambridge, UK) using a protocol previously optimized in terms of scoring function, rigid/flexible ligand and binding site, radius of the binding site, presence/absence of a water molecule (HOH846) within the binding site, number of genetic algorithm (GA) runs (Atanasova et al, 2015a, Atanasova et al, 2015b, Stavrakov et al, 2016, Stavrakov et al, 2017. The docking simulations in the present study were performed at the following settings: scoring function ChemPLP, flexible ligand, rigid protein, radius of the binding site 6Å, no water molecule, 100 GA runs.…”
Section: Docking Protocolmentioning
confidence: 99%